MAXIMIZING EMPLOYEE TURNOVER AS A STRATEGIC APPROACH TO EFFECTIVE MANAGEMENT: A STUDY OF SELECTED HOSPITALITY FIRMS IN OWERRI - DIALOKE, DR. IKECHUKWU; CHIMA, ANYANWU, PASCHAL (IJRDO - Journal of Applied Management Science, 2017)
this study focused on examining employee turnover as a strategic approach tomanagement effectiveness. In conducting the study, descriptive survey approach was adoptedand data was generated from a five point likert scale. The study covered a population of sixty(60) managers and supervisors of eleven (11) hospitality firms within the Owerri metropolis.Because of the smallness of the data, the entire population was used as its sample; however, outof the 60 questionnaires distributed, only 48 were correctly filled and returned; thereby given aquestionnaire return rate of 80%. The data gathered was analyzed with the kruskawalis (H) test.This study haven surveyed literatures and conducted empirical inquiry came to the conclusionthat employees turnover can be of both strategic benefit and challenge to managementeffectiveness. Following the findings and conclusion above, the study recommends that forturnover to yield desired positive result as a tool to enhancing management effectiveness, thefollowings should be considered; where it is needful to embark on involuntary turnover(disengagement), it must be done in phases in other to give room for the organizational memoryto be passed on successfully to the new employee and that firms should endeavor avoid buildingthe business capabilities around one personnel, rather it should be spread across board throughopen communication and participative management style. This will ensure that whenvoluntary employee turnover occurs; the firm can overcome the shock by effectively replacinghim through internal processes. This will also help to bridge leadership and succession gaps